2012
DOI: 10.1159/000345083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conventional Mouthrinses on Initial Bioadhesion to Enamel and Dentin in situ

Abstract: Aim: The study aimed to investigate the effect of a customary fluoride solution, containing sodium fluoride and amine fluoride, on initial biofilm formation on enamel and dentin in situ compared directly to chlorhexidine. Methods: Bovine enamel and dentin specimens were mounted on maxillary splints carried by 9 subjects. After 1 min of pellicle formation, rinses with tap water (control), chlorhexidine (meridol med CHX 0.2%, GABA) and a fluoride mouthrinse (elmex, GABA) were performed for 1 min. Subsequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 106 publications
8
56
0
1
Order By: Relevance
“…Therefore, it can be presumed that fluorine ions were not possible to detect although they might have been present at the surface of enamel. In an in situ study, Hannig et al [41] reported that no accumulation of fluoride was traceable on enamel surface immediately after application of fluoride mouthrinse. Having in mind the wellknown model of fluoride effect by the formation of a calcium fluoride layer, authors considered that fluoride layers were rapidly covered and masked by pellicle structures, which made them not detectable by the EDS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be presumed that fluorine ions were not possible to detect although they might have been present at the surface of enamel. In an in situ study, Hannig et al [41] reported that no accumulation of fluoride was traceable on enamel surface immediately after application of fluoride mouthrinse. Having in mind the wellknown model of fluoride effect by the formation of a calcium fluoride layer, authors considered that fluoride layers were rapidly covered and masked by pellicle structures, which made them not detectable by the EDS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed no antibacterial and antiadherent effects for CPP/ACP. The bioadhesion processes were determined in situ , considering that in vivo and in vitro conditions differ considerably [25]. The methodical approach, including bovine enamel and dentin specimens fixed to individual upper jaw splints, has already been used in previous studies [20, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Hannig et al [29] compared the effect of fluoride solution (100 ppm F as AmF and 150 ppm F as NaF) to 0.2% CHX (positive control) on biofilm adherence to enamel and dentin in situ after 8 h of 1 min-rinse. The bacterial viability and CFU for total microorganism were determined.…”
Section: Differentmentioning
confidence: 99%